Usefulness of a dedicated mouthpiece for the Valsalva maneuver to visualize the hypopharynx during transoral endoscopy - Minoru Kato; Yoshito Hayashi; Ryotaro Uema; Hirotsugu Saiki; Keiichi Kimura; Takanori Inoue; Akihiko Sakatani; Shunsuke Yoshii; Yoshiki Tsujii; Shinichiro Shinzaki; Eisuke Hida; Hideki Iijima; et al. (Endoscopy International Open, 2020)
Background and study aims Patients with esophageal squamous cell carcinoma (SCC) are at high risk of developing second primary SCCs in the hypopharynx. However, such second primary tumors are difficult to observe because of lumen closure. The Valsalva maneuver using a dedicated mouthpiece is a promising technique to visualize the hypopharynx during transoral endoscopy. In the current study, we investigated the utility of this method. Patients and methods The current study was a randomized, controlled, crossover trial. Patients with esophageal SCC were randomly assigned first to undergo pharyngeal observation using the dedicated mouthpiece followed by observation using a conventional mouthpiece, or vice versa. The primary endpoint was complete visualization of the hypopharynx, which was assessed blindly by three external evaluators. Results A total of 68 pharyngeal examinations were analyzed – 34 with the dedicated mouthpiece and 34 with a conventional mouthpiece. Complete visualization was achieved in 68 % of the examinations (23/34) using the dedicated mouthpiece, whereas none of the examinations using the conventional mouthpiece achieved complete visualization of the hypopharynx. Observation scores of the oropharynx were not significantly different between both types of examination (P = 0.50). No serious adverse events (AEs) occurred. Conclusions Endoscopic view of the hypopharynx was markedly improved by the Valsalva maneuver using the dedicated mouthpiece, with no serious AEs. This procedure should be included in the endoscopic examinations for the patients with esophageal SCCs.